From Welltop to Laptop? - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2008)
Over the past decade, soaring commodity prices have had a relatively minor impact on the overall level of prices, at least by historical standards. Whereas oil is twelve times more expensive now that it was in 1999, consumer prices in industrialized countries are only 20 per cent higher. This short note explains why the sluggish response of inflation may be about to change.
Keywords: 330; capital; high-tech; inflation; Middle East; oil prices; stagflation